Baseline survey report of the Strengthen PSNP Institutions and Resilience phase II (SPIR II) resilience food security activity in Ethiopia - Gilligan, Daniel O.; Hirvonen, Kalle; Leight, Jessica; Tambet, Heleene; Tesfaye, Haleluya (Implementer-Led Evaluation & Learning Associate Award, 2023)
The objective of this report is to present results from the baseline survey conducted as part of the Implementer-Led Evaluation and Learning (IMPEL) evaluation of SPIR II, a randomized controlled trial launched in 2022. The second phase of the Strengthen PSNP Institutions and Resilience (SPIR) Resilience Food Security Activity (RFSA) aims to enhance livelihoods, increase resilience to shocks, and improve food security and nutrition for rural households vulnerable to food insecurity in Ethiopia. The RFSA is situated within Ethiopia’s Productive Safety Net Program (PSNP), one of the largest safety net programs in Africa. Funded by USAID’s Bureau for Humanitarian Assistance (BHA), SPIR II is implemented by World Vision International (lead), CARE, and ORDA in the Amhara and Oromia regions of Ethiopia. The IMPEL SPIR II impact evaluation employs an experimental design with three arms, comparing two treatment combinations of livelihood and nutrition graduation model programming provided to PSNP beneficiaries relative to a control group receiving only PSNP transfers. The treatment assignment is randomized at kebele level in 234 kebeles. In the first arm (the control group), PSNP is implemented by the government with SPIR II support for the provision of cash and food transfers only (no supplemental programming). In the second arm, SPIR II programming is rolled out to PSNP beneficiary households in conjunction with nurturing care groups (NCGs) targeting enhanced infant and young child nutritional practices. In the third arm, PSNP beneficiary households receive SPIR II programming and NCGs, supplemented with additional targeted cash grants to pregnant and lactating women.